EVALUASI KESESUAIAN PENYIMPANAN OBAT LOOK ALIKE SOUND ALIKE DI GUDANG FARMASI SOEROJO HOSPITAL MAGELANG - Nok Ikrimah; Chilmia Nurul Fatiha; Fajar Dewi Maretasari (Nusantara Hasana Berdikari, 2022)
The hospital is one of the units that organizes pharmaceutical service, one of which is related to medicine storage. The storage is in accordance with standards assessed from physical disturbances or contents that damage the quality of drugs. Look Alike Sound Alike (LASA) is medication name with similar appearance and similar speech. LASA drugs storage can cause medication errors or serious consequences for patients if error. This study aimed to determine the storage of LASA (Look Alike Sound Alike) drugs at Soerojo Hospital Magelang. This is descriptive study with data collection trough observation by filling out a checklist form. This study evaluated the storage method in pharmacy warehouses compared with the standard based on Ministry of Health. The results showed that the storage of LASA drug at the Soerojo Hospital Magelang was in accordance with the regulations but had not been fully implemented, such as the LASA label marking was not affixed to the packaging and the distance between drugs was not given.